Terminology, Policy Foundations, Purpose And Position Of Pai In The National Education System - Jajat Darojat; Hafidin Nurhadi; Arif Rohman Hakim (International Journal of Social Research, 2026)
Human beings are pedagogical creatures who have the potential intellect, heart, and body to be educated and educated. It takes an understanding of education to be in accordance with the spirit of humanity and human needs. This article is a discussion of collaborative thinking from various points regarding the terminology, purpose and position of Islamic education. As an Islamic education figure, the author will present the views of Syed Muhammad Naquib Al Attas, Imam Al Ghazali, and other Islamic education experts. The research method in this article is qualitative with a library research approach. A study based on research on documents or texts derived from literature. From the results of the study, various Islamic educational technologies were found, namely Al Tarbiyah, al Tansyi'ah, al Ishlah, al Ta'dib or al Adab, al Tahzib, al Tazkiyyah, al Ta'lim, al Siyasah, al Nash wa al Irsyad, al Mau'idzah, and al Akhlak. This article outlines three terms of education in Islam, namely al Tarbiyah, Ta'lim and Ta'dib. Of the three terminologies, according to Naquib Al Attas, for education in Islam, it is more appropriate to use the term Ta'dib. This term is more humanistic and relevant to the subject of education, namely humans. Because basically education is for moral purposes. Even if it refers to the purpose for which man was created, which is to become a servant (abdullah) and a representative of God on earth (khalifatullah). Thus, according to Imam Al Ghazali, the purpose of education is divided into two, namely the special goal as the achievement of happiness in the hereafter (ukhrawi), and the general goal is the substance of human beings as noble beings on earth (worldly), therefore it must achieve benefits in human life in the world. The conclusion is that Islamic education is a means for students to form morals and piety in the context of happiness in this world and the hereafter. As part of National education, Islamic Religious Education is the most important part because of its role in filling the spiritual void of students, this is affirmed in Pancasila and the Indonesian State Law.